INTEGRAL EDUCATION IN THE BUDDHIST TRADITION - Ferrer, Albert (International Journal of Research -GRANTHAALAYAH, 2018)
Western scholarship and culture usually ignore the contributions from other civilizations, in the field of education even more clearly than anywhere else. While the advocates of integral education, for instance, pay attention to the Western pedagogues only, there has been a profound educational philosophy in other contexts such as the Indian or the Buddhist. This paper tries to open the Western educational scenario to the Buddhist tradition in particular, outlining some achievements like the Buddhist university of Nalanda that can certainly inspire and enrich the educational world, in Asia or in the West. Hence, this introductory paper wishes to contribute to the needed intercultural dialogue in Western education and scholarship.